N-Acetyl-L-Cysteine Protects Organ Function After Hemorrhagic Shock Combined With Seawater Immersion in Rats by Correcting Coagulopathy and Acidosis - Liu, Yiyan; Zhu, Yu; Zhang, Zisen; Bao, Daiqin; Deng, Haoyue; Liu, Liangming; Li, Tao (Frontiers in Physiology, 2022)
Background: The mortality of trauma combined with seawater immersion is higher than that of land injury, however research on how to treat this critical case and which treatments to adopt is lacking. Methods: The effect of the thiol compound, N-acetyl-L-Cysteine, on survival, acidosis, coagulopathy, vital signs, oxidative stress, and mitochondrial and multi-organ function, was assessed in a rat model of hemorrhagic shock combined with seawater immersion (Sea-Shock). Results: Hemorrhagic shock combined with seawater immersion caused severe lethal trial, multi-organ impairment, oxidative stress, and mitochondrial dysfunction. NAC (30 mg/kg) with Lactated Ringer's (LR) (2 x blood volume lost) significantly improved outcomes compared to LR or hetastarch (HES 130/0.4) alone. NAC significantly prolonged survival time to 52.48 +/- 30.09 h and increased 72 h survival rate to 11/16 (68%). NAC relieved metabolic acidosis and recovered the pH back to 7.33. NAC also restored coagulation, with APTT, PT and PT-INR decreased by 109.31%, 78.09% and 73.74%, respectively, while fibrinogen level increased 246.23% compared with untreated Sea-Shock. Administration of NAC markedly improved cardiac and liver function, with some improvement of kidney function. Conclusion: The addition of NAC to crystalloid resuscitation fluid alleviated oxidative stress, restored redox homeostasis, and provided multi-organ protection in the rat after Sea-Shock. NAC may be an effective therapeutic measure for hemorrhagic shock combined with seawater immersion.